Nonlinear micro income processes with macro shocks - Martín Almuzara; Manuel Arellano; Richard W. Blundell; Stéphane Bonhomme (Centre for Microdata Methods and Practice (cemmap), The Institute for Fiscal Studies (IFS), 2025)
We propose a nonlinear framework to study the dynamic transmission of aggregate and idiosyncratic shocks to household income that exploits both macro and micro data. Our approach allows us to examine empirically the following questions: (a) How do business-cycle fluctuations modulate the persistence of heterogeneous individual histories and the risk faced by households? (b) How do aggregate and idiosyncratic shocks propagate over time for households in different macro and micro states? (c) How do these shocks shape the cost of business-cycle risk? We develop new identification and estimation techniques, and provide a detailed empirical analysis combining macro time series for the U.S. and a time series of household panels from the PSID.
Keywords: 330; Income process; business cycle; persistence; exposure to aggregate shocks